WEB APPLICATION METHOD "3D EMOTION COMPOSITION IN SUPERVISION" APPROBATION - Lillā, Marta; Millere, Laura; Paiča, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The global pandemic has accelerated the development of the digital environment, face-to-face work is transferred online, so it is important to create tools adapted to the digital environment. The emergency of Covid-19 has raised the demand for online supervision. In supervision sessions, it is important to talk about experiencing emotions in a professional environment. Latvia lacks digital methods for working with emotions in supervision. The aim of the study was to adapt the 3DEC method, to create it as a web application for use in remote supervision and to approbate the web application "3D emotion composition in supervision" in individual online supervisions. The original method 3DEC is intended for the evaluation of emotional experience in the practice of art therapists (Lejstrauta, 2021; Vanadziņa, 2021). The theoretical basis of the 3DEC method is integrative and includes the following principles: visual representation of emotions in a visible symbolic form; play and play space (Winnicot, 2007); distancing as one of the cognitive emotion regulation strategies (Powers & LaBar, 2019). 3DEC is also based on the Adaptive Coping with Emotions Model (ACE Model) (Berking & Whitley, 2014). The adapted method “3D composition of emotions in supervision” (3DECS) is intended for work in online supervision with the aim to promote awareness of emotions, their understanding and self–reflection. Using distancing and view of other perspectives, the method helps the client to reflect and become aware of emotional experiences, as well as provides an educational function about the meaning of emotions. The 3DECS method develops emotional awareness and adaptive emotion regulation skills. Main results: 1) the web application has been tested and is designed to work with emotions in supervision; 2) the data of the approbation stage show that the web application is sufficiently simple and intuitive; 3) the web application is secure because no information about the customer and the customer's actions in the tool is stored; 4) there are no restrictions on the use of the web application in relation to the duration of the cooperation between the supervisor and the supervision client.